Induction of Human T-cell and Cytokine Responses Following Vaccination with a Novel Influenza Vaccine. Issue 1 (December 2018) - Skibinski, David; Jones, Leigh; Zhu, Yuan; Xue, Lin; Au, Bijin; Lee, Bernett; Naim, Ahmad; Lee, Audrey; Kaliaperumal, Nivashini; Low, Jenny; Lee, Lawrence; Poidinger, Michael; et al.
Abstract Cell mediated immunity plays a vital role in defense against influenza infection in humans. Less is known about the role of vaccine-induced cell mediated immunity and the cytokine responses elicited. We measured CD4+ and CD8+ T-cell reactivity in human subjects following vaccination with licensed trivalent influenza vaccine and a novel virus-like particle based vaccine. We detected influenza-specific CD4+ T-cell responses following vaccination with the licensed trivalent influenza vaccine and found that these correlated with antibody measurements. Administration of the novel virus-like particle based vaccine elicited influenza-specific CD4+ and CD8+ T-cell responses and the induction of the cytokines IFN-γ, IL-17A, IL17F, IL-5, IL-13, IL-9, IL-10 and IL-21. Pre-existing cytokine responses influenced the profile of the cytokine response elicited by vaccination. In a subset of individuals the VLP vaccine changed pre-vaccination production of type 2 cytokines such as IL-5 and IL-13 to a post-vaccination type 1 cytokine signature characterized by IFN-γ. A transcriptional signature to vaccination was found to correlate with antibody titer, IFN-γ production by T-cells and expression of a putative RNA helicase, DDX17, on the surface of immune cells.